'A Most Manly and Amusing Game': Australian Football and the Frontier Wars. Issue 3 (2nd July 2016) - Pascoe, Robert; Papalia, Gerardo
Abstract : Formed in the 1850s frontier contact zone, Australian Football owes more to the experiences of the skirmishes between white settlers and Indigenous Australians than is usually recognised. If we reassess the historical sources from a Deleuzo-Guattarian perspective, we observe that the 'Game of Our Own' is a mix of British and Indigenous styles of warfare. The four men who drafted the rules of this new 'most manly and amusing game' were misfits from British society who were seeking new lives on the frontier. Their code contained 'striating' features played across 'smooth' spaces. The football teams adopted totemic plants and animals in their nomenclature; the players were bedizened in costumes that spoke of Empire; the bloody Frontier Wars were in living memory of the players and their 'barrackers'.